2019
DOI: 10.14302/issn.2379-7835.ijn-19-2774
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Indigenous and Artisanal Coastal Nutrition, the SDG Imperative: A Suggested Renaissance of Ethics for Research and Tertiary Education in the Anthropocene Era

Abstract: Maternal nutrition is at the core of any principle-centered projection of Sustainable Development Goals.Without the developmental health of newborns -there is no quality future. Specifically, there are situations all around the globe where Indigenous and Artisanal coastal people suffer from maternal malnutrition inadvertently limiting future potentials in many locations that will be most challenged by climate change. Results from research with Artisanal Fisherfolk in the Philippines and analysis of harvest by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To progress, it would be useful to prioritize, particularly regarding social aspects of the SDGs that can complement the Philippines' biodiversity priority. In the Philippines, endemic childhood malnutrition is most acute in coastal fisherfolk communities (Capanzana et al 2018), which points to the need for setting maternalchild nutrition as an SDG national priority (Watts 2019). Previous research has indicated that Aurora has acute maternal malnutrition represented by protein intake that is less than 20 percent of national and international recommendations (PMNCH 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To progress, it would be useful to prioritize, particularly regarding social aspects of the SDGs that can complement the Philippines' biodiversity priority. In the Philippines, endemic childhood malnutrition is most acute in coastal fisherfolk communities (Capanzana et al 2018), which points to the need for setting maternalchild nutrition as an SDG national priority (Watts 2019). Previous research has indicated that Aurora has acute maternal malnutrition represented by protein intake that is less than 20 percent of national and international recommendations (PMNCH 2018).…”
Section: Introductionmentioning
confidence: 99%